Analysis of vehicle emissions due to traffic on the Tambun Bungai Street Palangkaraya - Lesmana, Rudy Yoga; Akbar, Reza Zulfikar; Faradila, Amelia (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Tambun Bungai street is located between Ahmad Yani and Diponegoro street. It has a significant level of congestion due to the presence of several schools, view place of worship and District Public Hospital. Motor vehicle activity produces exhaust gas emissions that cause air pollution resulting in a decrease in air quality. The purpose of this research to determine the magnitude of motor vehicle exhaust gas emissions in Tambun Bungai street and compare the results of the analysis of total vehicle emissions with permitted air quality standards. The methods are traffic counting survey and spot speed survey, then the analyze using an empirical calculation. Based on the results of the analysis it is known that the largest emissions of light vehicles occurring on Tambun Bungai street are CO of 1783,15 ppm and HC of 229,95 ppm at 07.45-08.00, PM of 7,14 and NOx of 29,68 pphm at 07.00-07.15. Then for the largest emissions of heavy vehicles occurred on Tambun Bungai street are CO of 0,63 ppm, HC of 0,28 ppm, PM of 257,80 and NOx of 82,71 pphm at 07.00-07.15. Overall the result of emissions total that compared to permitted quality standard shows that the results of the analysis of each type of pollutant exceeded the permissible air quality standards. These results can illustrate the amount of pollution that occurs and has exceeded the specified threshold so that the government can make policies that can be minimized it.